Routledge handbook of civil wars - Newman, Edward 1970-; DeRouen, Karl R. 1962- (Routledge handbooks, 2014)
This comprehensive new Handbook explores the significance and nature of armed intrastate conflict and civil war in the modern world. Civil wars and intrastate conflict represent the principal form of organised violence since the end of World War II, and certainly in the contemporary era. These conflicts have a huge impact and drive major political change within the societies in which they occur, as well as on an international scale. The global importance of recent intrastate and regional conflicts in Afghanistan, Pakistan, Iraq, Somalia, Nepal, Cote d'Ivoire, Syria and Libya -- amongst others -- has served to refocus academic and policy interest upon civil war. Drawing together contributions from key thinkers in the field who discuss the sources, causes, duration, nature and recurrence of civil wars, as well as their political meaning and international impact, the Handbook is organised into five key parts: Part I: Understanding and Explaining Civil Wars: Theoretical and Methodological Debates Part II: The Causes of Civil Wars Part III: The Nature and Impact of Civil Wars Part IV: International Dimensions Part V: Termination and Resolution of Civil Wars. Covering a wide range of topics including micro-level issues as well as broader debates, Routledge Handbook of Civil Wars will set a benchmark for future research in the field. This volume will be of much interest to students of civil wars and intrastate conflict, ethnic conflict, political violence, peace and conflict studies, security studies and IR in general.